Web server for augmented reality application for automated external defibrillator - Chua, Jing Yi (2017)
Automated External Defibrillator (AED), a light-weighted compact device that inspects the heart rhythm of the victim and transfer an electric shock to the heart if abnormal rhythm is detected in order to bring back a normal heart rhythm. Sudden Cardiac Death (SCD) is an unpredictable death caused by cardiac causes, which can be called as Sudden Cardiac Arrest (SCA). SCA occurs when the heart stops beating unpredictably and if immediate treatment with defibrillator is not performed within the next few minutes, the victim will not be able to survive. Every year, there were approximately 16,000 deaths and 23% were due to cardiac causes. Study has found that most of the cases occur outside hospital, often in the company of passerby and the survival rate is 13.8%, which means only 14 out of 100 people survive from SCA. Until now, many people still do not know the importance of AED whereby it can literally treat SCA with just one or two shocks and prevent Sudden Cardiac Arrest from causing Sudden Cardiac Death. Therefore, this project aims to create a website to educate users about AED and prevent SCA from occurring in NTU. Users can easily locate the nearest AED whenever there’s emergency medical situation. In order to let all users to have a better understanding of AED, game-based learning is implemented in the website. The website targets to prevent and reduce the chances of SCD and increase the Chain of Survival in Singapore.